PENENTUAN PATAHAN DAN TOPOGRAFI MOHO PADA DATA NOAA-FA BERBASIS FFT - Bagus Jaya Santosa, Sungkono (Jurnal Neutrino, 2010)
Regional Gravity NOAA-FA data analysis using several gradient methods has been conducted to determine the fracture and direction fault based on FFT. Fault can be qualitatively identified from a regional anomaly data, gradient Theta and  Normalized Standard Deviation (NSD)  is  trending  north-south.  Dominant  fracture  orientation  parallel  to  the  fault  is  only detectable by gradient Theta and NSD, but  more  obviously displayed on the gradient NSD. Furthermore, regional anomaly of  Gravity data  inverted to generate  Moho  topography. This inversion  using  FFT  based  algorithm  (Parker,  1972).  The  inversion  result  of  Moho  depths between 30-39  km.  In the Moho  topography, there is contrast  depth  difference, namely the Latitude -35 to -25 and Longitude -70 to -65, which is suspected as a fracture.Keyword: Gravity, FFT, Inversion, Fault, Fracture, Moho